"It Doesn't Feel Like a Job to Learn": Preservice Elementary Teachers' Perceptions of Dance-Themed Mathematics Education. Issue 4 (2nd October 2017) - An, Song A.; Kim, So Jung; Tillman, Daniel; Robertson, William; Juarez, Martha; Guo, Connie
ABSTRACT: A series of dance activities were introduced to preservice teachers ( n  = 76) to help them understand how mathematics concepts could be associated with dance performance and choreography processes. A total of 468 pieces of qualitative data were collected, including 147 online discussion entries with 248 follow-up comments, and 73 individual reflection essays. The main themes for the various benefits that emerged across the preservice teachers' reflections were: (1) improving students' dispositions toward mathematics and creating an enjoyable learning environment for reducing mathematics anxiety; (2) allowing students to develop their creativity and allowing teachers to meet different students' needs; and (3) developing students' conceptual understandings of mathematics through multiple types of connections, representations, and communication. The findings support practical approaches for teacher educators who wish to employ dance in instructing mathematics teaching methods to their preservice teachers.